Polyethylene-Based Bio-And Nanocomposites for Packaging Applications - Zapata-Ramirez, P (wiley, 2016)
Polyethylene is an outstanding polymer for packaging applications due to its excellent properties such as easy processability, excellent chemical resistance, high durability, flexibility, and low density. However, to fit the different requirements from the food industry and society, the PE behavior should be improved to overcome two main issues: poor biodegradability and low gas barrier behavior. Currently, these drawbacks are solved by mixing PE with either a biopolymer for improvements in the biodegradation or clay particles for high barrier properties, producing biocomposites and nanocomposites, respectively. However, over the past few years there has emerged a new concept joining these two concepts, meaning that PE can be blended with both biopolymers and nanoparticles to obtain bionanocomposites. PE bionanocomposites are defined as composites based on a PE matrix blended with both a biopolymer and a nanoparticle. These PE bionanocomposites present: biodegradation coming from the presence of biopolymer; high barrier behavior coming from the biopolymer phase and the nanoparticles; and low water uptake due to the high tortuosity rendered by nanoparticles. Moreover, they present a synergic effect coming from the improvement in the PE/biopolymer compatibility by the presence of nanoparticles, reducing the biophase size. This chapter introduces the main concepts and examples to understand these novel materials such as PE-based nanocomposites, PE-based biocomposites, and PE-based bionanocomposites. © 2016 Scrivener Publishing LLC.